Numerical modeling of the formation of Shackleton crater at the lunar south pole - Halim, Samuel; Barrett, Natasha; Boazman, Sarah; Gawronska, Aleksandra; Gilmour, Cosette; Harish; McCanaan, Kathryn; Satyakumar, Animireddi V.; Shah, Jahnavi; Kring, David A. (David Allen); orcid:0000-0003-3150-6787; orcid:0000-0002-3440-6282; et al. (Icarus, 2021)
The lunar south pole, on the rim of Shackleton crater, is the target for the next human landing on the Moon. We use numerical modeling to investigate the formation of that crater and the distribution of ejecta around the south pole. We find that a 1.5 km diameter asteroid with a chondrite-like composition, vertically impacting a gabbroic anorthositic target at 15 km/s, forms a crater morphologically similar to Shackleton. If the impact had a shallower 45-degree trajectory, the asteroid may have had a diameter of 1.75 km and velocity of 15 km/s or a diameter of 1.5 km and velocity of 20 km/s. Impact melt is generated during the impact, with most of the melt volume ponding on the crater floor. We introduce a water-bearing layer at various depths in the target and find that the burial depth of a volatile layer influences the final crater morphology and may explain the morphology of Shackleton.